2010
DOI: 10.1007/s00520-010-1006-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the efficacy of bereavement life review therapy for spiritual well-being: a qualitative analysis

Abstract: Factors like "good memories of families," "loss and reconstruction," and "pleasant memories of last days" were associated with the improvement of spiritual well-being of bereaved families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…For three studies, two papers were reported on the same study protocol. [8910111213] Three studies used a mixed methods approach and thus were included in both categories [Figure 3]. The most common interventions used were life review, short life review, dignity therapy, and bereaved life review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For three studies, two papers were reported on the same study protocol. [8910111213] Three studies used a mixed methods approach and thus were included in both categories [Figure 3]. The most common interventions used were life review, short life review, dignity therapy, and bereaved life review.…”
Section: Resultsmentioning
confidence: 99%
“…Within the 18 included studies providing qualitative data, we found 2 reports[912] with qualitative evaluations from RCTs,[815] 15 other studies,[111720222526272829303132333435] and 1 qualitative evaluation of transcripts of dignity therapy. [36] In addition to the reports from RCTs, three studies followed a mixed methods approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About the categories for the important things, family caregivers recognized the importance of family relationships or relationships with people. Bereaved family members who took care of a loved one also perceived that "family" was important (Ando, Morita, Miyashita, Sanjyo, Kira, & Shima, 2011). In usual busy life, we forget importance, we may rethink what is important when people confront traumatic problems.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Guilt may interfere with adjustment to bereavement over time 46 and response to psychological treatments. 48 Assessing guilt in bereavement and interventions targeting guilt may be beneficial for some individuals.…”
Section: Bereavement Challenges and Adjustment To Lossmentioning
confidence: 99%